Herding Behavior in The Stock Market: A Literature Review - Adik Duwi Rahayu; Aditya Putra; Chiata Oktaverina; Regina Aulia Ningtyas (Epistemik Press, 2020)
This article aims to prove the existence of herding behavior in a number of stock markets in various parts of the world and find out the factors that cause herding behavior. The method used in this article is a research library by taking data from 80 international journals and 4 local journals. The results of our analysis conclude that herding behavior occurs in almost all stock markets in the world. Factors that cause herding behavior include negative news sentiments towards stocks, incentives and career concerns owned by analysts, market risk and firm level uncertainty, market uncertainty, extreme market conditions, periods of high information flow, risk of volatility, analysis of more types of stocks small, economic / financial crisis, declining market conditions, rising interest rates, currency depreciation, poor information environment, and low quality disclosures. The limitation of this article is that the amount of data taken from the results of research in several stock markets is uneven, such as the lack of data retrieval from the stock market on the American continent.